Beach Clean Up: Sebuah Pemasaran Sosial Guna Meningkatkan Kesadaran Pengelolaan Lingkungan Pesisir - Asmaul Husna; Yuhdi Fahrimal; Dara Quthni Effida; Ramadhani Ramadhani; Ainal Fitri (Universitas Teuku Umar, 2023)
Batee Puteh Beach, West Aceh Regency is a beach tourism object that has historical value, but in recent years this beach has had quite a serious problem with trash around its coast. Therefore it is deemed necessary to carry out a community service program in the form of joint action to clean up the Batee Puteh Beach area by knowing Beach Clean Up which can involve various elements including students, tourists, the youth community who are environmentalists, and local residents who are willing to be involved as volunteers. The implementation of this service began with the delivery of material on social marketing, the concept of Coastal Cleanup, followed by dividing the participants into several small groups consisting of 6 people and distributing them to several points around the coast of Batee Puteh Beach. Each group will clear the area for 30 meters. After the activity, service participants understood the importance of cleanliness and management of the coastal environment, and as many as 90 percent of participants also stated that the quantity of waste and pollution had been visibly reduced.